30 A new protocol for sonographic evaluation of mid-portion achilles tendinopathy: a test retest intra and inter-rater reliability study. (April 2019) - Haleem, MSc Zubair; Kelly, Stephen; Pyne, Dev; Lack, Simon; Morrissey, Dylan
Abstract : Introduction: Achilles tendinopathy (AT) is common and recalcitrant. A new ultrasound Achilles tendon assessment protocol has been developed as part of a large RCT. Ultrasound scanning has considerable operator dependence hence this study was designed to investigate inter-rater and intra-rater reliability in symptomatic individuals. Method: Twenty-three participants (18 with AT, 10 female) were recruited and independently examined by two clinicians of varied experience. Measures of Achilles thickness, neovascularity, plantaris position and size, intratendinous tears (ITT) presence, fascia crura tear (FCT) presence, calcification, insertional elements and ultrasound provocation tests were recorded. Inter-rater and intra-rater reliability was assessed using Intraclass correlation coefficients (ICC), Standard error measurements (SEM) and minimal detectable changes (MDC) along with percentage agreements. Results: Excellent levels of inter- and intra-rater reliability were found for thickness (Intra-rater ICC 0.88–0.99, SEM 0.15–0.37, Inter-rater ICC 0.87–0.98 SEM 0.22–0.60), neovascularity (Intra-rater ICC 0.96–0.96, SEM 0.28–0.40, Inter-rater ICC 0.91–0.94 SEM 0.49–0.50) and 100% agreement on insertional findings, ITT, FCT and US provocation tests. 67%–91% agreement was found on presence, position and size of plantaris. Conclusions: The new protocol demonstrates excellent inter- and intra-rater reliability thus minimising operator dependence and is suitable for objective assessment. Further development of methods to identify the presence, position and size of the plantaris tendon is recommended.